THE INFLUENCE OF ORGANIZATIONAL COMMUNICATION AND LEADERSHIP FACTORS ON THE PERFORMANCE OF EMPLOYEE - Heru Kreshna Reza; Sukmo Hadi Nugroho (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT This research background of the company's efforts to improve the performance of employees is a goal to be achieved by the company. Performance is highly dependent on the awareness of each employee. To improve the performance of employees of the company must to maintain the existence of human resources one of the efforts made is to improve employee performance by creating leadership and good communication with employees.The purpose of this study are: 1) To determine the influence of leadership on employee performance 2) To determine the effect of organizational communication on employee performance and 3) To determine the influence of leadership and organizational communication together on employee performance. The population in this study were all employees of a Government Organization, amounting to 35 people. Data analysis technique used in this research is descriptive statistical analysis with multiple regression analysis methodBased on the results of research and discussion that has been done then it can be concluded as follows: 1) Leadership significant effect on employee performance of a Government Organization 2) Organizational communication significant effect on employee performance a Government Organization 3) Leadership and organizational communication significant jointly to the performance of employees of Government Organization Keywords : Leadership, Communication and Employee Performance